Stamped from the beginning : a graphic history of racist ideas in America - Gill, Joel Christian; Kendi, Ibram X. (Ten Speed Press, 2023)
"A comprehensive history of anti-black racism in graphic-novel format focuses on the lives of five major players in American history and highlights the debates that took place between assimilationists and segregationists and between racists and anti-racists."--